2004
DOI: 10.1128/cmr.17.4.729-759.2004
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathogenesis of Oropharyngeal Candidiasis in Human Immunodeficiency Virus Infection

Abstract: Oropharyngeal and esophageal candidiases remain significant causes of morbidity in human immunodeficiency virus (HIV)-infected patients, despite the dramatic ability of antiretroviral therapy to reconstitute immunity. Notable advances have been achieved in understanding, at the molecular level, the relationships between the progression of HIV infection, the acquisition, maintenance, and clonality of oral candidal populations, and the emergence of antifungal resistance. However, the critical immunological defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
192
0
17

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(217 citation statements)
references
References 465 publications
(555 reference statements)
1
192
0
17
Order By: Relevance
“…Thus, the model closely reproduces the mucosal candidiasis found in HIV/AIDS patients. Indeed, among these patients, esophagus and GI tract are strongly colonized while systemic dissemination rarely occurs (27,28). Our results in RAG-2 Ϫ/Ϫ mice are in line with other studies using SCID mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the model closely reproduces the mucosal candidiasis found in HIV/AIDS patients. Indeed, among these patients, esophagus and GI tract are strongly colonized while systemic dissemination rarely occurs (27,28). Our results in RAG-2 Ϫ/Ϫ mice are in line with other studies using SCID mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, under conditions of immune disruption, C. albicans can rapidly transition into a pathogen, causing an array of mucosal and disseminated infections with high mortality (de Repentigny et al, 2004). As a polymorphic species, C. albicans is capable of switching morphology between yeast and hyphal forms, a transition crucial to its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Histatin proteins demonstrate broad spectrum antifungal activity against pathogenic fungi like Candida spp, Cryptococcus neoformans and Aspergillus fumigatus [10]. Edgerton et al [11] reported anti candidal activity of histatin 5.…”
Section: Innate Immunitymentioning
confidence: 99%
“…In addition, it also damages the fungal cell wall and activates intracellular autolytic enzymes [10].…”
Section: Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation